Предмет: Алгебра,
автор: gurgen777
Помогите решить пожалуйста
Приложения:
Ответы
Автор ответа:
0
1-ое x2-5x+1=(x-4)
x2-5x+1-x+4=0
x2+6x+5=0
x2 - 6x + 5 = 0
D = (-6)2 - 4·1·5 = 16
x1 = 6 - √16 = 12·1
x2 = 6 + √16 = 52·1
x2-5x+1-x+4=0
x2+6x+5=0
x2 - 6x + 5 = 0
D = (-6)2 - 4·1·5 = 16
x1 = 6 - √16 = 12·1
x2 = 6 + √16 = 52·1
Автор ответа:
0
x1 = 6 - √16 = 1
2•1
x2 = 6 + √16 = 5
2•1
2•1
x2 = 6 + √16 = 5
2•1
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Английский язык,
автор: jambolatjambolat509
Предмет: Другие предметы,
автор: Аноним
Предмет: Математика,
автор: улым